Pizza and pizza chefs in Japan : a case of culinary globalization - Ceccarini, Rossella (Social sciences in Asia ;, 2011)
Scholars have extensively studied the entry of restaurant chains such as McDonald's into Asia and their reception, while attention has also been paid to ethnic restaurants as agents of cultural globalization. But what about the globalization of artisanal foods led by professional workers themselves? This book looks at artisanal pizza in Japan as a cultural object globalized and domesticated through the agency of the food producer, and shows that not only the food, but also the craftsperson, is going global. The volume analyzes the reception of pizza in Japan, the transnational flow of pizza ch.